The meaning of the Japanese emperor in japan’s constitutional system - Eto, Shohei (Đại học Quốc Gia Hà Nội, 2020)
This paper is intended to discuss the meaning of the Japanese Emperor in Japan’s constitutional system. Many scholars in Japan have long argued that the existence of the Emperor is incompatible with the Constitution’s principle of popular sovereignty because the legitimacy of the Emperor ultimately resides in the Shinto religion, not the people. Yet, it seems that the former Emperor, Akihito, who has just abdicated managed to succeed in thriving his status as the nation’s symbol by way of committing to the fundamental values of the Constitution, especially its Pacifist character. He did so by performing activities such as consoling the souls of the war dead and visiting victims in disaster-stricken areas. Some experts welcomed his new role, saying that the Emperor had shown us that the monarchy and the people can co-exist. But this argument is problematic. The Constitution only allows the Emperor to perform formal and ceremonial acts and his new role may exceed his constitutional authority as it may amount to the task of personal “integration” as Rudolf Smend once argued. The question is whether this integrational function can be the Emperor’s legitimate task under the principle of popular sovereignty. This paper intends to answer this question by focusing on the question of symbolism in the Constitution.